Instability modulation and novel optical soliton solutions to the Gerdjikov-Ivanov equation with M-fractional - Ismael, Hajar F. F.; Baskonus, Haci Mehmet; Bulut, Hasan; Gao, Wei (Springer, 2023)
The modified exponential function method is used to obtain some new analytical solutions of the nonlinear Gerdjikov-Ivanov equation with the M-fractional operator. The novel obtained solutions are expressed in hyperbolic, trigonometric, and exponential function forms. Moreover, the instability modulation and gain spectra of the Gerdjikov-Ivanov equation are also analyzed. Constraints conditions are utilized to verify the existence of the solutions. Presented solutions are novel, satisfy and verify the M-fractional Gerdjikov-Ivanov equation.
Keywords: Optical soliton solutions; Gerdjikov-Ivanov equation; modified exponential function method; M-fractional